Cu-catalyzed cascade difluoroalkylation/5-endo cyclization/β-fluorine cleavage of ynones. Issue 13 (25th January 2023) - Su, Jingwen; Guo, Wenbin; Liu, Yi; Kong, Lichun; Zheng, Hanliang; Zhu, Gangguo
Abstract : A Cu-catalyzed cascade difluoroalkylation/5- endo cyclization/β-fluorine cleavage of ynones is reported, delivering α-monofluoroalkenyl cyclopentanones with high efficiency and stereoselectivity. Abstract : A copper-catalyzed, redox-neutral cascade difluoroalkylation/5- endo annulation/β-fluorine cleavage of ynones is developed, providing a direct and stereoselective method to access synthetically important α-monofluoroalkenyl cyclopentanones. Mechanistic studies suggest an unprecedented Cu II -assisted β-fluorine fragmentation, which may be valuable for the challenging but important C–F bond activation. Moreover, the in situ generated difluorocarbene was found to serve as an effective reductant for the regeneration of copper(i ) catalyst, thus avoiding the addition of external reductants.